ANALISIS PENGARUH PENGANGGARAN PARTISIPATIF, INFORMASI ASIMETRIS, DAN MOTIVASI KARYAWAN TERHADAP SENJANGAN ANGGARAN PADA BANK BUMN DI INDONESIA - Antonius Bimo Rentor; Yenni Carolina (COMPETITIVE, 2020)
Some issues on budget are appear in many forms at banking industry especially in Indonesia. One of the issues that related to the budget is marked by efforts of the employee to create space in budgeting. This issue called as a budgetary slack. The purpose of this research is to analyze various factors that influence budgetary slack. These factors include participatory budgeting, asymmetric information, and employee motivation. The data collection techniques used in this research were questionnaires. Meanwhile, the analytical method used in this study is PLS 'Partial Least Square'. The conclusion of the study is that the participatory budgeting variable has no effect on the budgetary slack variable. Meanwhile, asymmetric information variables and employee motivation variables were each stated to influence budgetary slack variables. Keywords: Budgetary Slack, Participatory Budgeting, Asymmetric Information, and Employee Motivation.